Mental health problems among healthcare professionals following the workplace violence issue-mediating effect of risk perception - Zhong, Deping; Liu, Chengcheng; Luan, Chunna; Li, Wei; Cui, Jiuwei; Shi, Hanping; Zhang, Qiang (Frontiers in Psychology, 2022)
Although there have been numerous studies on mental well-being impairment or other negative consequences of Workplace Violence (WPV) against healthcare professionals, however, the effects of WPV are not limited to those who experience WPV in person, but those who exposed to WPV information indirectly. In the aftermath of “death of Dr. Yang Wen”, a cross-sectional study was conducted to explore the psychological status of healthcare professionals. A total of 965 healthcare professionals from 32 provinces in China participated in our research. The prevalence rates of Post-Traumatic Stress Disorder (PTSD) symptoms, depression, anxiety among healthcare professional in the current study were 25.60%, 46.01%, and 27.88%, respectively. Moreover, our research suggested that the awareness of WPV-incident had a significant association with PTSD symptoms. In addition, risk perception was shown to mediate the effect of WPV awareness on PTSD symptoms. Furthermore, the present research also found a U-shaped relationship between issue salience and PTSD symptoms, and the relationship between issue salience and anxiety, indicating that higher awareness of WPV issue was negatively related to mental health status (including PTSD and anxiety) but only to the points at which there were no additional effects of more issue salience. This study highlighted that more protective measures for healthcare professionals need to be implemented in response to potential WPV events. More importantly, risk perception was found to mediate the effect of WPV issue salience on PTSD symptoms, it is critical to reduce the mental health burden through intervening in risk perception.